Bad Kitty Goes to the Vet: Bad Kitty #9 - Bruel, Nick (New York : Roaring Brook Press, 2016)
"Even the best bad kitties can get sick, and when it happens, it means just one thing: a visit to the vet!"--.
"A Neal Porter Book."
Keywords: JUVENILE FICTION / Animals / Cats; JUVENILE NONFICTION / Humor / General; Cats -- Fiction; Veterinarians -- Fiction; Humorous fiction